IDENTIFICATION OF ASPERGILLUS SP MUSHROOMS IN WHEAT FLOUR SOLD OPENLY IN CIROYOM MARKET AS RAW MATERIALS FOR HALAL AND MUNGLE-FREE - Fitri Rahmi Fadhilah; Ally Kafesa; Sopi Napita (Universitas Mathla’ul Anwar Banten, 2021)
Wheat flour is used as the main ingredient of food which is often used by the wider community, one of which is as an ingredient for making various kinds of food products. Wheat flour is included in food products safe and halal for consumption. The wheat flour which is sold openly is packaged in transparent plastic. With the easy-to-open packaging, it is easy for microorganisms to enter the flour, one of them is fungus. This study was aim to determine the types of Aspergillus sp in wheat flour which is sold openly in the Ciroyom Market. Method The research used is descriptive by using 30 samples of wheat flour which are sold openly in the Ciroyom Market. This research was conducted in the laboratory of the Rajawali Health Institute, Bandung. Result and Discussion: The results of this study showed the presence of Aspergillus flavus (50%), Aspergillus fumigatus (50%), Aspergillus niger (16.7%), Aspergillus terreus (3.3%) and negative (26.7%) Aspergillus sp. Conclusion: From this research, it can be concluded that the species of Aspergillus flavus, Aspergillus fumigatus, Aspergillus niger and Aspergillus terreus were found so we can conclude that the wheat flour that is sold openly is still a halal product but it is not mushroom-free products.